The pathogenesis of post-primary tuberculosis. A game changer for vaccine development. (May 2019) - Hunter, Robert; Actor, Jeffrey
Abstract: A vaccine that prevents transmission of infection is urgently needed in the fight against tuberculosis (TB). Results of clinical trials have been disappointing. Major problems include lack of biomarkers and understanding of the mechanisms of disease and protection. A more fundamental problem is that the scientific community seldom recognizes that primary and post-primary TB are distinct disease entities. Nearly all vaccine candidates have been designed and tested in models of primary TB, while transmission of infection is mediated by post-primary TB. Post-primary TB is seldom studied because no animal develop complete symptoms of the disease as it exists in humans. Nevertheless, mice, guinea pigs and rabbits all develop infections that at certain points appear to be models of human post-primary TB. Slowly progressive pulmonary TB in immunocompetent mice is an example. It is characterized by an alveolitis with infected foamy macrophages that have multiple characteristics of the human disease. We demonstrated that inclusion of an immune modulating agent, lactoferrin, with a BCG vaccine in this model induced a sustained reduction in lung pathology, but not numbers of organisms in tissue. Since the animals die of expanding pathology, this demonstrates the feasibility of using selected animal models for studies of vaccines against post-primary TB.